Effects of increased feed intake in early gestation on sow farrowing performance and offspring carcass characteristics - R E Musser; Duane L Davis; M Heintz; J Bauman; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1999)
Three hundred and ninety-four PIC sows were used to determine the effects of increased feed intake during two critical stages of fetal development on farrowing performance and offspring carcass characteristics. Sows were fed 8 Ibid for one of three periods, d 10 to 30, d 30 to 50, or d 10 to 50 of gestation in comparison to a control level of 4 Ibid. Treatments did not affect the number of pigs farrowed. Sows fed 8 Ibid of complete diet from d 10 to 30 of gestation tended to have offspring with heavier hot carcass weight (P = .16) compared to offspring of other sows. Sows fed 8 Ibid of feed from d 30 to 50 produced offspring with greater backfat and decreased percentage lean than offspring of other sows. Effects observed in the carcass characteristics are inconsistent with previous findings, and more research is needed to determine the reason why these responses occurred.; Swine Day, Manhattan, KS, November 18, 1999
Keywords: Swine day; 1999; Kansas Agricultural Experiment Station contribution; no. 00-103-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 841; Swine; Gestation; Feed intake; Off-spring